Study of the problems of development of entrepreneurial structures during the economic crisis - A. B. Meshcheryakova (Путеводитель предпринимателя)
Economic crises as an object of study are of concern to more than one generation of economists. Modern problems associated with crises relate to many aspects of life, including entrepreneurial activity. At all times, the issues of survival of entrepreneurs in the conditions of the economic crisis have been given a significant role, however, scientists have not developed universal solutions on how enterprises should act in crisis conditions. Various processes, and, first of all, political ones, have a significant impact on the ability of a business to develop in crisis conditions. Under these conditions, the development of effective solutions for the development of business structures in a crisis implies the need for closer interaction between business and the state. The subject of the research is the approaches to the development of entrepreneurial structures in the conditions of the economic crisis. The article substantiates the need for joint work of the state and business structures in a period when the latter are in crisis conditions. The need to protect their own interests of business forces entrepreneurial structures to sacrifice the national interests of the state on whose territory they operate. And here the state should make efforts to achieve its own goals on the basis of partnership with the business environment.